Neurturin Evokes MAPK-Dependent Upregulation of Egr4 and KCC2 in Developing Neurons - Anastasia Ludwig; Pavel Uvarov; Christophe Pellegrino; Judith Thomas-Crusells; Sebastian Schuchmann; Mart Saarma; Matti S. Airaksinen; Claudio Rivera (Neural Plasticity)
The K-Cl cotransporter KCC2 plays a crucial role in the functional development of GABAA-mediated responses rendering GABA hyperpolarizing in adult neurons. We have previously shown that BDNF upregulates KCC2 in immature neurons through the transcription factor Egr4. The effect of BDNF on Egr4 and KCC2 was shown to be dependent on the activation of ERK1/2. Here we demonstrate that the trophic factor neurturin can also trigger Egr4 expression and upregulate KCC2 in an ERK1/2-dependent manner. These results show that Egr4 is an important component in the mechanism for trophic factor-mediated upregulation of KCC2 in immature neurons involving the activation of specific intracellular pathways common to BDNF and Neurturin.